STUDI PERKEMBANGAN WILAYAH DAN DAYA DUKUNG LINGKUNGAN KEPARIWISATAAN DI WILAYAH YOGYAKARTA UTARA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The tourism region grawth often indicates the decline of the environmental carrying capacity, including the conflict consequence in the carrying capacity and the spatial use. The un-control of the spatial grawth and resources advantages is the effect of the increasing development policy that cause the damage of the environmental function. The spatial and natural resources advantage is neededfor the consideration of the carrying capacity. A research is needed to define the safeguard traffic in connection with that problem. It is also important t9 be analyzed to the region carrying capacity that can define the tolerance border and the flexibility of capacity. The long purpose is too fulfill the tourists satisfactions in this area. The study sample is taken from 4 villages' area in Pakem region (Kaliurang Area) and the Merapi Volcano National Park (TNGM) DIY province. There are 2 variables considered: (1) the region grawth